The Improvement of Reproductive Health Knowledge (Vaginal Discharge and Menstrual Pain) of Women - Nonik Ayu Wantini; Zahrah Zakiya; Silvia Dewi Styaningrum (Journal of Ners and Midwifery, 2021)
Vaginal discharge and menstrual pain are problems that are often faced by women. Women should be able to distinguish between physiological and pathological vaginal discharge, physiological and pathological menstrual pain. Based on the results of previous studies, most women have insufficient knowledge about vaginal discharge and menstrual pain. Health education is an effort to overcome these problems. The purpose of this study was to determine reproductive health care habits, history of menstrual pain and vaginal discharge, differences in knowledge about reproductive health, especially vaginal discharge and menstrual pain before and after health education was given. This study was a quasi-experimental design with one group pre test-post test. The sample was 27 women in Setan Hamlet, Maguwoharjo, Depok, Sleman who were selected by purposive sampling. The instrument used a questionnaire. The data analysis used paired sample t-test. The results showed that 66.7% had carried out routine genetalia care, 29.6% routinely used feminine cleansing soap, 25.9% experienced menstrual pain, vaginal discharge as much as 37%. The mean knowledge before health education was 48.70 (SD 23.59), while the mean knowledge after health education was 87.59 (SD 6.84). There is a difference between knowledge about reproductive health before and after health education is given (p-value = 0.000). The conclusion is that health education increases knowledge about reproductive health.